The Implementation Of Wordwall Platform to Deliver Interactive Medium for Students' Vocabulary in SDN 1 Jeringo - Saumi, Fadila Komaris; Boniesta Zulandha Melani; Lalu Ali Wardana; Dewi Satria Elmiana (Journal of Classroom Action Research, 2025)
This study investigates the implementation of the Wordwall platform as an interactive medium for enhancing vocabulary learning among fifth-grade students at SDN 1 Jeringo. The study was driven by changes introduced through the 13 Curriculum, which resulted in the elimination of English lessons in early grades and limited access to adequate learning tools. Since 2022, the Merdeka Curriculum has been implemented, reintroducing the English subject to elementary school students. The Merdeka Curriculum is an educational reform introduced by Indonesia's Ministry of Education, Culture, Research, and Technology (Kemdikbudristek) in 2022. This curriculum marks a transition toward a more adaptable, learner-focused, and skills-oriented approach to teaching and learning. SDN 1 Jeringo, as one of the Sekolah Penggerak, has started reintroducing English through the Merdeka Curriculum in grades 3 and 5, although students still struggle due to insufficient resources and prior exposure. A pre-experimental research design with a one-group pretest-posttest model was conducted involving 26 students. Vocabulary tests created using the Wordwall platform were administered before and after the intervention. The activities included matching games and picture-word association tasks, conducted in three sessions over three days. The average vocabulary score increased significantly from 60.77 (pretest) to 83.46 (posttest), with a practical gain of 22.69 points. The normality of the data was confirmed using the Shapiro-Wilk test. A paired sample t-test, performed in SPSS 26, showed a statistically significant improvement (p < 0.05). These findings suggest that Wordwall is an effective, engaging, and accessible tool for vocabulary learning in primary education, especially in the context of the Merdeka Curriculum.